Exploring the heterogeneity of hepatic and pancreatic fat deposition in obesity: implications for metabolic health - Deng, Ming; Li, Zhen; Chen, Shangyu; Wang, Huawei; Sun, Li; Tang, Jun; Luo, Liman; Zhang, Xiaoxiao; Xu, Haibo; Dai, Zhe (Frontiers in Endocrinology, 2024)
Objective This retrospective observational study investigates the heterogeneity of hepatic and pancreatic fat deposition and its implications for metabolic health in individuals with obesity. Methods A total of 706 patients with obesity underwent an MRI to quantify liver and pancreatic fat. Patients were classified into four groups based on fat deposition: no fat (None), fatty pancreas only (NAFPD), fatty liver only (NAFLD), and both conditions (NAFLD+NAFPD). Biochemical profiles, insulin resistance (Homeostatic Model Assessment for Insulin Resistance, HOMA-IR), and β-cell function were analyzed. A series of multiple linear regressions were used to investigate the independent effects of characteristics on glucose, insulin, and C-peptide at 0h. Another multiple linear regression was performed to evaluate the effects of basic characteristics on average liver fat, mean pancreatic fat, and visceral fat. Results The majority (76.63%) exhibited both NAFLD and NAFPD, highlighting the heterogeneity of fat deposition among individuals with obesity. Groups with fatty liver displayed significantly higher fasting glucose, insulin, C-peptide, and HOMA-IR levels than those without fatty liver (P < 0.01). Fatty pancreas alone did not significantly influence these metabolic parameters (P > 0.05). This underscores the greater metabolic impact of hepatic fat compared to pancreatic fat. Conclusions The study confirms the complex heterogeneity of fat deposition in obesity, with the fatty liver being a more influential factor in metabolic disturbances than the fatty pancreas. The prevalent co-occurrence of NAFLD and NAFPD in this population underscores the need for targeted management strategies focusing on hepatic fat reduction to mitigate metabolic risk.